Understanding Well Load-up Behaviour in CO2 Wells During CO2 Back-production Field Test at the Ketzin Pilot Site, Germany – Turner Criterion Revisited. (July 2017) - Liebscher, Axel; Wiese, Bernd; Möller, Fabian; Bannach, Andreas
Abstract: A CO2 back-production test was performed at the pilot site for geological CO2 storage at Ketzin, Germany. Over thirteen days 240 tons of CO2 were safely back-produced from the reservoir; 55 m 3 of saline reservoir fluid was continuously co-produced. Throughout different rate stages of the back-production experiment downhole pressure conditions were very stable and the gas/fluid ratio remained constant, indicating that no well load-up occurred. The calculated minimum flow velocities based on the standard Turner criterion are, however, up to one order of magnitude higher than the actual flow velocities. Thus, a modified Turner parameterization is required for CO2 -dominated well.